(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article presents the results of the analysis of the transparency of the ownership structure of commercial banks in Ukraine. It has been determined that opaque structures of ownership of commercial banks have negative consequences: excessive lending to related parties and withdrawal of funds from banks through such operations, increased risks of banks that include the business risks of the owner of the bank and related persons, decrease in efficiency and stability commercial banks, low level of trust in the banking system of Ukraine. The legal requirement to disclose only the holders of significant participation allowed the banks to assert that they did not have significant holders and thus concealed the real beneficiaries. A typical non-transparent property structure scheme was a structure using offshore. In the part of banks, the ultimate nominal owner is a citizen of offshore jurisdiction, which is associated with the Ukrainian real owner of the trust agreement. In calculating the level of transparency of the ownership structure of commercial banks in Ukraine, a transparent ownership share was considered to be directly or indirectly owned by the state, an individual or a public company, and the data of which are indicated. The analysis showed that large banks and the majority of medium-sized banks had high level of transparency of ownership structure while final owner was known in a number of small and medium-sized banks. In the dynamics, the level of transparency of bank capital has increased, where a sharp increase in the indicator is observed in the second half of 2015, after the adoption of changes in regulatory acts aimed at disclosing the structures of ownership of commercial banks and increasing transparency.